EVALUATING THE REPEATABILITY OF RTK GPS - Pirti, A. (MANEY PUBLISHING, 2011)
Real Time Kinematic GPS System (RTK GPS) measurements like other survey measurements are not devoid of errors. The purpose of this study is to show that RTK results can seriously be degraded by obstructions such as trees and the baseline length. This paper shows the investigations of the two positioning error sources, studying their effects, and searching for methods to decrease, or possibly eliminate these two errors in order to achieve better positioning accuracies in RTK GPS. As stated above, one of the major problems is the signal attenuation which occurs when GPS signals are attenuated by shades of trees or leaves. Another problem associated with RTK positioning is the baseline length which tends to degrade the accuracy as the baseline length increases. On the other hand, this study investigates the achievable accuracy and repeatability of the RTK under different satellite configurations by using different reference points. Accuracy of spatial data is reported according to the National Standard for Spatial Data Accuracy of United States (NSSDA).
Keywords: Repeatability; RTK GPS; Signal attenuation; Baseline length; Satellite configurations; Engineering; Geology; Remote Sensing